'To work more, produce more and defend the revolution': Copper workers from socialism to neoliberalism. (1st June 2021) - Whitaker, Georgia; Vergara, Ángela
Abstract : On 11 July 1971, Chile's National Congress, in a historic vote, unanimously approved reforming the constitution, which opened the door to nationalise the large-scale copper industry. Traditional historical accounts of the nationalisation of copper had emphasised a history of negotiations between foreign capital and the Chilean government, documenting how economists and political leaders experimented with different approaches to obtain a share of the profits from the country's most valuable commodity. By focusing exclusively on the political economy, however, scholars have overlooked the role of workers during and after the process of nationalisation and failed to account for why copper miners continued to fight to protect a state-owned company. Influenced by Peter Winn's Weavers of Revolution and recent studies on people's experience during the Popular Unity (UP) era, this article looks at the nationalisation of copper from below. It analyses how workers fought for, understood and experienced the nationalisation; how the UP transformed labour relations at the local level; and how the military, after 1973, redesigned the state company. By placing workers at the centre of the nationalisation, this article can help better understand its importance as a matter of both political economy and workers' power and explain why the copper mines became the first site of labour resistance against the military regime.